(untitled) (Revista Brasileira Multidisciplinar, 2020)
Enteric tablets are preparations developed with a polymeric coating that is insoluble in acid media in order to protect unstable drugs of the action of gastric acid. Thus, it’s relevant the development of gastro-resistant coated tablets containing ibuprofen since this drug is able to cause gastric irritability due to the decrease of the protective prostaglandins production related to the mucus synthesis. Therefore this research aimed to develop enteric coated tablets containing ibuprofen by dry and wet vias and to perform the quality control tests, for example, average weight, disintegration, hardness and friability in order to verify if the tablets developed complies standards established by Brazilian Pharmacopoeia sixth edition (2019). The methodology used was the compression method for obtaining ibuprofen tablets by dry via and wet via with cellulose acetate phthalate coating. After coating, quality control tests were performed: average weight, hardness, friability and desintegration. The results showed the importance of the study of preformulation and formulation in the development of ibuprofen tablets as well as the importance of the study of the preformulation and the formulation of the enteric coating solution and the study of its production to guarantee the quality of the final product, in this case, gastro-resistant tablets. The parameters evaluated in the quality control assays indicated that the gastro-resistant ibuprofen tablets obtained by dry via are in accordance with the pharmacopeia specifications. On the other hand, the gastro-resistant tablets of ibuprofen obtained by wet via showed unsatisfactory results in terms of average weight which suggests an error in filling the matrix and adjusting of the lower and upper punctures. Thereby, the ibuprofen tablets obtained by dry via showed better quality which means that this method of preparation of gastrorresistant tablets is safer for the population.